Effects of annealing processing on the oxide derived Cu2ZnSn(Sx, Se1−x)4 thin films. (December 2016) - Chen, Guilin; Wu, Miaoju; Wang, Weihuang; Zhang, Jin; Lin, Limei; Liu, Jinyang; Lai, Fachun
Abstract: To reveal the effects of annealing conditions on the formation mechanisms of Cu2 ZnSn(Sx, Se1−x )4 (CZTSSe) and the related secondary phases, and improve the crystallization of the films simultaneously, different annealing processing was studied. In this work, the uniform Cu-Zn-Sn oxides precursors have been grown on glass substrates by doctor blade. Whereafter, those precursor films were sulfurized first and then selenized at different temperatures to prepare high-quality pure phase CZTSSe absorber films. The effects of annealing conditions on structural, morphological and optical properties of CZTSSe films have been investigated. Meanwhile, XRD, SEM and Roman studies revealed that the CZTSSe samples sulfurized at 420 °C for 30 min first and then selenized at 540 °C for 20 min are optimum films as an absorbed layer.